STUDI KOMPARATIF METODE PERESAP BUATAN UNTUK PENGENDALIAN LIMPASAN AIR HUJAN DI PERMUKIMAN PERKOTAAN: KASUS KELURAHAN LEBAKGEDE KECAMATAN COBLONG, KOTA BANDUNG - Arwin S. (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2006)
Densely urbanized area required solution to control rainwater run-off in the form of water recharge techniques which was efficient and effective. One of the most conducive water recharge techniques in densely urbanized was recharge well. In general the well design could be compared to pursuant to its wall construction, which might vary in porosity. Based on determination of those methods of recharge well dimension, it was found that Sunjoto method use dynamic approach and yields well dimension which was relatively small. There were three types of suggested recharge wells. The selection of the recharge well types was in accordance to the condition of local area. Each typical well had advantages and disadvantages. At limited backyard area, it was suggested to apply recharge well design (Type II), which some part of the well wall was impervious and the other part was pervious. In road area, it was suggested to use recharge well (Type I), with permeable bottom and all wall was made from brick. In the relatively wide backyard, it was suggested to use recharge well (Type III), where the entire wall was porous.